2011
DOI: 10.1520/jai103304
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Knee Wear, Kinematics, and Particle Morphology Among Different Bearing Geometries in a Mobile Bearing Knee System

Abstract: Excellent clinical long term results were reported from individual clinical centers for both of the two fundamental design principles—fixed and mobile bearing knee designs. Several pre-clinical studies are dealing with a direct comparison between fixed and mobile bearing knee replacements, but to our knowledge there is no published data comparing the in vitro wear and kinematic behaviour of mobile bearing designs with floating, rotating and posterior stabilized gliding surfaces. The objective of our study was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Several factors may have contributed to the relatively low rate of complications in this pilot study: the surgical technique with attention to soft tissue balancing [3], the innovative design of the prosthesis, and the computer-assisted navigation system [22]. Biomechanical investigations conducted in vitro showed that the gravimetric wear rate for the e.motion ® UC prosthesis was 2.3 mg/106 cycles [4], which is relatively low compared with the wear rates of mobile-bearing designs with good long-term clinical outcome (6.6 to 16 mg/106 cycles) [1, 23, 24]. This is a promising result for the e.motion ® UC prosthesis, considering the long-term survivorship of an implant is related to the wear of the bearing surface [25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several factors may have contributed to the relatively low rate of complications in this pilot study: the surgical technique with attention to soft tissue balancing [3], the innovative design of the prosthesis, and the computer-assisted navigation system [22]. Biomechanical investigations conducted in vitro showed that the gravimetric wear rate for the e.motion ® UC prosthesis was 2.3 mg/106 cycles [4], which is relatively low compared with the wear rates of mobile-bearing designs with good long-term clinical outcome (6.6 to 16 mg/106 cycles) [1, 23, 24]. This is a promising result for the e.motion ® UC prosthesis, considering the long-term survivorship of an implant is related to the wear of the bearing surface [25].…”
Section: Discussionmentioning
confidence: 99%
“…The objectives of this new implant are to avoid contact stress peaks while providing good stability and mobility also in the absence of a posterior cruciate ligament. More specifically, the constant distal radius from -5° to 90° of flexion allows high stability in the midstance phase through a constant ligament tension, thereby reducing the incidence of paradox movement [4]. The primary objective of this pilot study was to assess the general functionality of the e.motion ® UC prosthesis in daily life activities, 5.6 years after the TKA index surgery.…”
Section: Introductionmentioning
confidence: 99%
“…It might be argued that multidirectional mobility has been associated with higher risk of PE wear [23]. However, this design has shown to decrease the PE wear in in vitro simulation [14, 30]. Other authors observed no significant osteolysis after implantation of either unidirectional or multidirectional mobile‐bearing TKR [25, 26].…”
Section: Discussionmentioning
confidence: 99%